2022
DOI: 10.1111/1755-0998.13670
|View full text |Cite
|
Sign up to set email alerts
|

Using haematophagous fly blood meals to study the diversity of blood‐borne pathogens infecting wild mammals

Abstract: Many emerging infectious diseases originate from wild animals, so there is a profound need for surveillance and monitoring of their pathogens. However, the practical difficulty of sample acquisition from wild animals tends to limit the feasibility and effectiveness of such surveys. Xenosurveillance, using blood‐feeding invertebrates to obtain tissue samples from wild animals and then detect their pathogens, is a promising method to do so. Here, we describe the use of tsetse fly blood meals to determine (direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To reduce costs and increase our sample sizes, we used a fly pooling strategy. Pooling has drawbacks when studying pathogen ecology, in particular when looking for mammal host–pathogen detection correlations to assign a pathogen to a particular host or vector species, since it is not possible to make sure that host and pathogen DNA stem from a same individual fly (Alfano et al, 2021; Mwakasungula et al, 2022). This problem is even complicated by potential DNA movements in the collection tube before the analyses, which might increase the frequency of spurious codetection events.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce costs and increase our sample sizes, we used a fly pooling strategy. Pooling has drawbacks when studying pathogen ecology, in particular when looking for mammal host–pathogen detection correlations to assign a pathogen to a particular host or vector species, since it is not possible to make sure that host and pathogen DNA stem from a same individual fly (Alfano et al, 2021; Mwakasungula et al, 2022). This problem is even complicated by potential DNA movements in the collection tube before the analyses, which might increase the frequency of spurious codetection events.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of virus in a population does not necessarily relate to transmission. Mosquitoes will often be incidental carriers of pathogens circulating in the environment and may not be responsible for transmission [10][11][12] . There is no "smoking gun" in terms of transmission proofs from eld-collections of vertebrates or mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Haematophagous insects can yield information on local pathogen prevalence without being part of the transmission cycle. For example, collections of tsetse ies in Tanzania 10 and Culex mosquitoes in the Brazilian Amazon 11 yielded malaria parasites while urban Culex collections identi ed dengue, Zika and chikungunya viruses in Pernambuco, Brazil 12 .The presence of non-vector-borne pathogens, such as hepatitis C virus 8 and H5N1 virus 13 have also been noted in mosquito collections. Xeno-surveillance might also be used to detect vertebrate antibodies to pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…As tsetse flies are easy to trap (little or no specific expertise required), this method will allow the simultaneous and long-term monitoring in different Sub-Saharan Africa areas. The interest of this method is increased by several studies showing that blood meals could also be used to detect circulating antibodies against specific viruses, thus broadening the information obtained from blood meals [23,47,48]. Overall, tsetse flybased xenosurveillance could be very useful to monitor the circulation of enzootic viruses in the wild and at wild/human interfaces in future One Heath programs in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as their host preference is often restricted to a limited number of vertebrate species, different mosquito species would be needed to cover all vertebrate wildlife. Alternatively, previous studies in Gabon [22] and Tanzania [23] have shown the interest of tsetse flies to obtain the blood of the vertebrates they bite (mostly mammals, but also birds and reptiles) for the screening of bloodborne pathogens, particularly in Sub-Saharan Africa where Glossinidae are present. As, tsetse flies take large blood meals (ranging from 20 μL up to 100 μL for the largest species) for their activity and reproduction [24], they are useful for blood sampling without affecting wildlife.…”
Section: Introductionmentioning
confidence: 99%